Economic outcomes of government-assisted refugees in designated destinations: The effect of city size - Yasmin Gure; Garnett Picot; Feng Hou (Economic and Social Reports)
A key component of Canada’s immigration program is to promote the balanced geographic distribution of immigrants and refugees across Canada. This study asks whether there were significant differences in the economic outcomes of government assisted refugees (GARs), based on the size of the city to which they were designated. The analysis was conducted for both those remaining in the designated cities (stayers) and those moving to other locations (movers).